IODINE AND THE THYROID : III. THE SPECIFIC ACTION OF IODINE IN ACCELERATING AMPHIBIAN METAMORPHOSIS. - Swingle, W. W. (The Rockefeller University Press, 1919)
1. Amphibian metamorphosis depends upon the amount of iodine secured by the larvæ; the greater the quantity the more rapid the differentiation. 2. Bromine is physiologically inert when fed even in large quantities to frog larvæ, hence it cannot be substituted for iodine. Bromine feeding has no effect on the thyroid. 3. Iodine is the active constituent of the thyroid gland, in the Anura at any rate, and functions within the body by stimulating intracellular oxidations; it is apparently specific in its action. 4. The basal metabolism of patients suffering from athyreosis, whose metabolism is 40 per cent below normal, is very likely held at this figure and prevented from sinking lower to the death point by the introduction of iodine into the body through food and water. 5. The thyroid gland is an organ the function of which is the extraction from the circulation, storage, and supplying to the organism, under the pressure of its needs, the small quantities of iodine taken into the body. The chief function of this gland then is the utilization of iodine in small quantities.